Regulation of IgM+ B Cell Activities by Rainbow Trout APRIL Reveals Specific Effects of This Cytokine in Lower Vertebrates - Soleto, Irene; Morel, Esther; Martín, Diana; Granja, Aitor G.; Tafalla, Carolina (Frontiers in Immunology, 2018)
Tumor necrosis factor ligand superfamily members such as B cell activating factor (BAFF) and a proliferation-inducing ligand (APRIL) have been identified in mammals as key regulators of B cell homeostasis and activation. However, the immune functions of APRIL are not as well defined as those of BAFF. Furthermore, while BAFF is present in all vertebrates, APRIL is missing in some animal groups, suggesting that BAFF has compensated the functions of APRIL in these species. In this context, we thought of great interest to explore the effects of APRIL on teleost B cells, given that APRIL appears for the first time in evolution in bony fish. Thus, in this study, we have performed an extensive analysis of the effect of APRIL on B cells using rainbow trout (Oncorhynchus mykiss) as a model species. Our results demonstrate that APRIL induces a specific proliferation of IgM+ B cells by itself and increases IgM secretion without promoting a terminal differentiation to plasma cells. APRIL also increased the levels of surface MHC II and augmented the capacity of these cells to process antigen, effects that were exclusively exerted on IgM+ B cells. Although our results point to a highly conserved role of APRIL on B cell homeostasis and activation throughout evolution, some specific differential effects have been observed in fish in comparison to the effects of APRIL previously described in mammals. Finally, the effects that APRIL induces on rainbow trout IgM+ B cells described in this paper have been compared with those previously reported in response to BAFF.